OBTAINING THE FAIR VALUE OF PELITA RAYA STREET BUNTOK SOUTH BARITO REGENCY - Nanang Sentot Harjanto; Wafik, Ahmad Zaenal (Universitas Mataram, 2023)
The assessment was set out to determine the fair value of Pelita Raya Street Buntok, South Barito Regency. This research is considered important due to the BPK's findings that revealed the weaknesses of the Internal Control System in the preparation of financial statements in which the recording and management of Fixed Assets have not been fully adequate. The assessment phase is divided into two assessments, the assessment of road components and the assessment of land under the road. The road component valuation uses a Cost Approach/DRC (Depreciated Replacement Cost) approach with a unit in place cost calculation method. Land under the road is assessed using the Market Data Comparison Method by using regression analysis (quality rating model). The analysis showed that the Fair Value of Pelita Raya Street was Rp24,816,825,000.00. The Fair Value of the road component is Rp15,196,584,000.00 and the Fair Value of land under the road is Rp9,620,241,000.00.